Impacts of Bilingual Education on Secondary School Grades, Attendance, Retentions and Drop-Out - Herman Curiel; James A. Rosenthal; Herbert G. Richek (Hispanic Journal of Behavioral Sciences, 1986)
Junior high and high school academic performance of two groups of students were compared in a quasi-experimental study. The experimental group students (N = 86) had received one or more years of bilingual instruction at the elementary level while the control group students (N = 90) had not participated in an elementary bilingual program. While differences in grade-point average (GPA) and absenteeism were small, the bilinguals were less likely to drop-out and experienced fewer retentions. Secondary analyses focused on the relationships within the experimental group between number of years enrolled in bilingual programs and secondary school outcomes. The relationships of number of years to ab-senteeism and to retention were quite weak. Important relationships between number of years and GPA and between number of years and drop-out were observed. As number of years increased, mean GPA in 7th, 8th and 9th grades increased and the probability of drop-out decreased.